Komunikasi Interpersonal Pada Komunitas Dakwah Binaan Nusukan Dari MTA Dalam Membentuk Ukhuwah - Fatkhul Putra Perdana; Rina Sari Kusuma (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
This research is motivated by Indonesia as a predominantly Muslim country, giving rise to a variety of da'wah organizations such as the Majlis Tafsir Al- Qur'an (MTA). The presence of this community organization gave rise to the model of brotherhood formation through the stages of interpersonal communication. This research is a descriptive qualitative research and uses the population of all members of the Nusukan fostered community from MTA. The sampling used is the snowball sampling model. Data collection uses in-depth interviews, documentation and observation. Data validity uses triangulation of data sources. The results of this study are the stages of forming ukhuwah. First, Ta'aruf, which occurs as the initial stage of effective interpersonal communication, involves the stages of contact and orientation. Second, Tafahum as a means of understanding deeper between members through interpersonal communication involves the stages of involvement. Third, ta'awun as interpersonal communication in fostering mutual care which includes the stages of involvement but tends towards the stages of familiarity. Fourth, takaful in interpersonal communication so as to form a sense of brotherhood covering the stages of intimacy and improvement. Penelitian ini dilatarbelakangi dengan Indonesia sebagai negara yang mayoritas Islam, sehingga memunculkan berbagai macam organisasi dakwah seperti MTA. Kehadiran Organisasi masyarakat ini memunculkan model pembentukan persaudaraan melalui tahapan-tahapan komunikasi interpersonal. Penelitian ini merupakan penelitian kualitatif deskriptif dan menggunakan Populasi seluruh anggota komunitas Binaan Nusukan dari MTA. Teknik sampling yang digunakan adalah model snowball sampling. Pengumpulan data menggunakan wawancara mendalam, dokumentasi dan observasi. Validitas data menggunakan triangulasi sumber data. Hasil dari penelitian ini adalah ditemukannya tahapan-tahapan pembentukan ukhuwah. Pertama, ta’aruf yang terjadi sebagai tahap awal komunikasi interpersonal yang efektif itu meliputi tahapan kontak dan orientasi. Kedua, tafahum sebagai sarana dalam memahami lebih dalam antaranggota melalui komunikasi interpersonal meliputi tahapan keterlibatan. Ketiga, ta’awun sebagai komunikasi interpersonal dalam menumbuhkan rasa saling peduli yang meliputi tahapan keterlibatan tetapi cenderung menuju tahapan keakraban. Keempat, takaful dalam komunikasi interpersonal sehingga membentuk rasa persaudaraan meliputi tahapan keakraban dan perbaikan.